Chronicler's women - a holistic appraisal - F. Olojede (Acta Theologica)
This article attempts to fill, in part, the gap in scholarship on the role of women in the book of Chronicles by providing data to show that the Chronicler succeeded in highlighting the roles and status of women in ancient Israel, as he copiously employed materials that are otherwise unknown in the biblical text and modified his Vorlage. A relentless focus on kinship and familial ties is discernible in the analysis of the roles and positions of the women who are presented in a way that shows their affinities to the people (or land) of Israel. It is argued that the Chronicler was intent on showing that women – all kinds of women – were a solid part of Israel’s story and of its identity that was being redefined and reconstituted. Besides affirming his concept of laer'f.yI-lk', the Chronicler’s presentation clearly reflects the changing sociocultural patterns of his time, especially in relation to exilic/post-exilic Israelite women.